Three dimensional printing: A review on the utility within medicine and otolaryngology. (October 2016) - Kaye, Rachel; Goldstein, Todd; Zeltsman, David; Grande, Daniel A.; Smith, Lee P.
Abstract: Three dimensional (3D) printing is a novel technique that has evolved over the past 35 years and has the potential to revolutionize the field of medicine with its inherent advantages of customizability and the ability to create complex shapes with precision. It has been used extensively within the fields of orthopedics, dentistry, and craniofacial reconstruction with wide ranging utility including, medical modeling, surgical planning and the production of custom plates, screws and surgical guides. Furthermore, it has been used for similar means in the field of Otorhinolaryngology and also has potential to revolutionize the treatment of airway malacia. In fact, 3D printed external tracheal splints have already been studied in several pediatric patients with very promising results. The emerging field of 3D bioprinting, which integrates tissue engineering with 3D printing, may produce a paradigm shift with the potential introduction of customized functional biologic replacements.